INTERNATIONAL MEASURES TO COUNTERACT THE LAUNDERING OF ILLEGAL INCOME OF THE FIFTH GENERATION – LEGAL CONDITIONS FOR STRENGTHENING THE SECURITY OF THE FINANCIAL MARKET - I. V. Vashchekina; A. N. Vashchekin (Вестник университета, 2021)
The article analyses the development of international agreements on the means of controlling financial activities, concluded to counteract the laundering of proceeds from crime and the financing of terrorism. The study was carried out by analytical methods based on domestic legislation, international agreements and regulations. As a result of thirty years of work on organizing interaction in the developing three-level financial monitoring system, a whole set of measures has developed, the main development trend of which is to reduce information uncertainty. In this regard, the fifth generation of agreements on the limitation of potentially illegal activities in the financial sector, introduced in 2020, is acquiring special importance. The legal entities covered by the restrictive and control measures now include crypto exchange platforms, virtual wallet providers, as well as firms that provide currency exchange services. In a number of areas, information is automatically exchanged about ongoing transactions, as well as about their participants – clients of banks, insurance and brokerage companies, investment funds, in order to prevent aggressive tax planning and make it difficult to access unjustified tax breaks. The paper presents the economic and organizational results of the introduced legal measures.